IDENTIFIKASI POTENSI WISATA DESA TANGKUP KARANGASEM MENUJU DESA WISATA RINTISAN - Ni Wayan Mekarini; Putu Agus Prayogi; I Ketut Sutapa (Synergy and Society Service, 2021)
Tangkup Village has an area of 2,667 Km2, most of which is in the form of rice fields. The natural tourism potential of Tangkup Village is a rice field area located in Tangkup Anyar, a watershed located in Tangkup Desa area, and green hills that surround the village. Cultural potential in the form of cagcag woven cloth which is a typical product of Tangkup, traditional snacks called jaje tulud, tipat pesor and sangait. In other places, sangait is made from sweet potatoes, Sangait in Tangkup village is made from cassava which is widely grown by local people. However, in the process of developing this snack product, it encountered obstacles related to the dough that did not support the process of design tulud cakes with coconut shells. Even though the community wants to develop jaja tulud, the tools used should not be replaced. Because of these difficulties, not many residents survive to make jaja tulud which is usually used for ceremonial needs. Regarding its function as a typical snack, students want to develop this snack so that it can be of economic value and accepted by tourists through a more elegant presentation. Students are actively involved in the preparation for the formation of Pokdarwis so that the direction of village development is towards a managed and directed tourism village. So far, the potential management of Tangkup Village is still being handled independently by utilizing the land owned, especially those located near watersheds, in the form of cafes, rafting, Asta Gangga Park attractions and bamboo houses that are being built as tourist facilities on the hill. The village hopes that students will help generate the tourism potential of Tangkup Village, so that it is widely known and visitors enjoy the beauty of this beautiful fertile village through the preparation of local human resources to welcome Tangkup village which will soon become a tourist village.